2013
DOI: 10.1371/journal.pone.0075579
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and High-Throughput Quantitation Assay of the Nuclear Factor κB Activity Using Fluorescence Correlation Spectroscopy in the Setting of Clinical Laboratories

Abstract: BackgroundTranscription factor nuclear factor-κB (NF-κB) plays a key role in the regulation of immune responses to inflammation. However, convenient assay systems to quantitate the NF-κB activity level in a timely manner are not available in the setting of clinical laboratories. Therefore, we developed a novel and high-throughput quantitative assay based on fluorescence correlation spectroscopy (FCS) to detect the NF-κB activity level in cellular nuclear extracts and evaluated the performance of this method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A transient reporter assay and EMSA showed that VND7 binds to the 53‐bp X1E1 sequence of the XCP1 promoter (from −148 to −96 bp; Yamaguchi et al ., ; Figure S1b). In this study, we first aimed to define which nucleotides within the X1E1 sequence are critical for interaction with VND7 by using FCS, which allowed us to determine the status of the interaction between DNA and proteins quantitatively (Kinjo and Rigler, ; Wölcke et al ., ; Kobayashi et al ., ; Octobre et al ., ; Veprintsev and Fersht, ; Harada et al ., ). For the FCS analysis, we prepared a maltose‐binding protein (MBP)‐tagged C‐terminally truncated VND7 protein containing the whole NAC domain (amino acid residues 1–161; MBP‐VND7 1–161 ; Yamaguchi et al ., , ; Endo et al ., ) and the 138‐bp promoter fragment of XCP1 (from −233 to −96 bp) labeled with a fluorescent dye, 5(6)‐carboxytetramethylrhodamine (TAMRA) (TAMRA‐ XCP1 pro).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…A transient reporter assay and EMSA showed that VND7 binds to the 53‐bp X1E1 sequence of the XCP1 promoter (from −148 to −96 bp; Yamaguchi et al ., ; Figure S1b). In this study, we first aimed to define which nucleotides within the X1E1 sequence are critical for interaction with VND7 by using FCS, which allowed us to determine the status of the interaction between DNA and proteins quantitatively (Kinjo and Rigler, ; Wölcke et al ., ; Kobayashi et al ., ; Octobre et al ., ; Veprintsev and Fersht, ; Harada et al ., ). For the FCS analysis, we prepared a maltose‐binding protein (MBP)‐tagged C‐terminally truncated VND7 protein containing the whole NAC domain (amino acid residues 1–161; MBP‐VND7 1–161 ; Yamaguchi et al ., , ; Endo et al ., ) and the 138‐bp promoter fragment of XCP1 (from −233 to −96 bp) labeled with a fluorescent dye, 5(6)‐carboxytetramethylrhodamine (TAMRA) (TAMRA‐ XCP1 pro).…”
Section: Resultsmentioning
confidence: 97%
“…However, SPR is considered to be suitable for the detailed analysis of only limited numbers of protein and/or DNA samples, because the molecules need to be immobilized on the sensor chips (Helwa and Hoheisel, ). In contrast, FCS not only is a quantitative method for analyzing the affinity between transcription factors and DNAs, but also has the advantage in analyzing a large number of samples because the protein and DNA molecules are simply mixed in a solution at small scale (Kinjo and Rigler, ; Wölcke et al ., ; Kobayashi et al ., ; Octobre et al ., ; Veprintsev and Fersht, ; Harada et al ., ). Therefore, a variety of different sets of competitor fragments can be used for FCS, which is thus suitable for high‐resolution analysis of cis ‐acting sequences responsible for binding to the specific proteins.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations